ANALISIS PERBANDINGAN METODE PERHITUNGAN PAJAK PENGHASILAN PASAL 21 GAJI PEGAWAI TETAP TERHADAP PROFITABILITAS PT. ANUGERAH JAYA - Lidia Andiani; Fenny Devina Gunawan; marli marli (MEASUREMENT : Jurnal Program Studi Akuntansi, 2023)
The purpose of this study is to determine the level of company profitability by using the calculation method of Income Tax (PPh) 21 Gross Up Method and Net Basis Method as a comparison. The analytical method used in this thesis research is a qualitative descriptive method. The results showed that using the Net Basis Method increased the company's profitability by 10.81% compared to using the Gross Up Method with a value of 10.7%.